A New Approach for Solving Cell Formation Problem Considering Alternative Process Routings - Payam Chiniforooshan; Behrooz Pourghannad; Narges Shahraki (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2011)
In this paper, a mathematical model is proposed to solve cell formation problem considering alternative process routings in which more than one process route for each part can be selected. The model attempts to minimize intercellular movements and incorporates several real-life production factors and practical constraints. In order to increase the flexibility provided by the multiplicity of routings, the model distributes production volume of each part among alternative routes. Also, a constraint enforcing work load balancing among machines is included in the model. Due to the complexity and combinatorial nature of this model, an enhanced algorithm comprised of a genetic algorithm and a linear programming is proposed for solving the model. The proposed algorithm is tested by a range of test problems and compared with two algorithms from the literature .The computational results show that the proposed algorithm is effective and the proposed approach offers better solution.